KAJIAN KERAGAMAN GENETIK GEN PENYANDI Cytochrome c Oxidase Sub-unit 3 (COX3) PADA Tarsius bancanus borneanus, Tarsius bancanus bancanus DAN Tarsius spectrum - , ADI PARAMARTA; , Dr. drh. Rini Widayanti, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tarsius is one of Indonesiaâs endemic primate which are endangered. Morphological among the species almost be same that become constrains to identification. Information about these different characteristics each species is expected to captivity. Molecular exploration is one of the efforts to differentiate of species Tarsius. The main objective of this research is to analyze the genetic diversity of Cytochrome c oxidase subunit 3 (COX3) encoding gene of Tarsius bancanus bancanus, Tarsius bancanus borneanus and Tarsius spectrum. The DNA samples isolated from muscle of Tarsius bancanus bancanus, Tarsius bancanus borneanus dan Tarsius spectrum. Amplification segment of COX3 gene by PCR technique used primer COX3 F and COX3 R for Tarsius bancanus bancanus and Tarsius bancanus borneanus produced 952 bp length of DNA segment. Amplification segment of COX3 gene for Tarsius spectrum using primer COX3 bF and COX3 bR produced 1069 bp length of DNA segment. The result of PCR reaction followed by sequencing. The result of COX3 gene sequences then would be analized using MEGA version 5.1 program. Result of analyze showed 148 sites of different nucleotide, 38 sites of different amino acid and three sites of nuclotide and two sites of amino acid occurs deletion. Average of genetic distances based on nucleotide sequence of COX3 genes analyzed using Kimura 2-parameter found the value of 9,7%. Construction of phylogenetic tress used Neighbor-Joining method unable to distinguish between Tarsius bancanus bancanus (from Sumatra), Tarsius bancanus borneanus (from Kalimantan) and Tarsius spectrum (from North Sulawesi).